The study of affective value in educational video production style using kansei engineering method - Nur Faraha Bte Hj. Mohd. Naim; Ag. Asri Ag. Ibrahim (2020)
ABSTRACT This paper presents the emotional responses among higher institution learners towards the production style of an educational video. The video design concepts for each production style were categorized into three sections, non-linear video with visual effects (interactive video mobile-learning), linear video with visual effects (green screen) and linear video with no visual effects (screencast). The Kansei Engineering approach was used to measure the learners’ emotion reaction on each of the production style. Through Kansei Engineering method, the outcomes presented variance of active and passive emotion reaction towards the production style, difference feelings responses caused by the video design, whereas at the end most learners agreed that the inclusion of interactivity and aesthetics in video design will increase their motivation to learn from the educational video.